1999
DOI: 10.1074/jbc.274.17.11817
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Unusual pH Dependence of Plastocyanin from the Fern Dryopteris crassirhizoma

Abstract: Spectroscopic properties, amino acid sequence, electron transfer kinetics, and crystal structures of the oxidized (at 1.7 Å resolution) and reduced form (at 1.8 Å resolution) of a novel plastocyanin from the fern Dryopteris crassirhizoma are presented. Kinetic studies show that the reduced form of Dryopteris plastocyanin remains redox-active at low pH, under conditions where the oxidation of the reduced form of other plastocyanins is inhibited by the protonation of a solvent-exposed active site residue, His 87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 45 publications
(63 reference statements)
3
114
0
Order By: Relevance
“…The molecular environment of the metalloprotein active site and weak interactions with the surrounding groups may modulate the properties of the metal center. For example, the coordinated imidazole ring in cytochrome c peroxidase is hydrogen bonded to a neighboring aspartic acid residue [6] and that in plastocyanin from fern undergoes p-p stacking with a phenylalanine residue [7,8], and the interactions are considered to affect the redox potential of the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular environment of the metalloprotein active site and weak interactions with the surrounding groups may modulate the properties of the metal center. For example, the coordinated imidazole ring in cytochrome c peroxidase is hydrogen bonded to a neighboring aspartic acid residue [6] and that in plastocyanin from fern undergoes p-p stacking with a phenylalanine residue [7,8], and the interactions are considered to affect the redox potential of the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…W290G crystallized in a space group P6 5 22, with a very long c axis, requiring the detector to be moved further from the crystal, limiting the resolution of the data to 2.2 Å. The diffraction images were integrated using the HKL suite (54), scaled and merged in SCALEPACK and subsequently processed with CCP4.…”
Section: X-ray Crystallographic Data Collection and Structure Determimentioning
confidence: 99%
“…ribonucleotide reductase is especially pertinent where alteration of the hydrophobic environment of the tyrosyl radical by mutation of second coordination sphere residues dramatically lowers radical stability (19;20). Additionally, substantial evidence now indicates that second coordination shell effects in metalloproteins may profoundly influence the reactivity and electronic structure of active-site metal ions while weak interactions (such as hydrogen bonds) have been strategically manipulated to control reactivity in proteins and model complexes (21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…It has been previously reported that fern Pc conserves both the same global structure and negative electrostatic character of eukaryotic Pcs, but its acidic region has moved from the canonical east position and is surrounding the hydrophobic ET north site, this change resulting in very distinct electrostatic and steric properties [45,46]. Thus, the unusual structure of Dryopteris Pc impedes an efficient interaction with diatom PSI, as previously described in its interaction with spinach PSI [46], confirming that fern Pc has followed a relatively independent evolutionary pathway since ferns diverged from other vascular plants [45,46].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, whereas diatom PSI is able to effectively bind eukaryotic acidic Pcs, although with a minor ET efficiency as compared with Phaeodactylum Cyt ( Fig. 1 and Table 1), both the positively-charged Nostoc Pc and the fern Pc, in which the relocation of the acidic region results in very distinct electrostatic properties [45,46], showed a drastic decrease in the affinity and the ET efficiency to PSI. Finally, the absence of a detectable fast phase when any Pc acts as electron donor to diatom PSI points to the subtle and precise interactions involved in the rearrangement process leading to the optimized configuration for ET in the native Cyt/PSI diatom couple [17].…”
Section: Kinetic Analysismentioning
confidence: 87%